Natural fruit peels - potential biosorbents for combating oil pollution / Wan Nazihah Wan Ibrahim, Nordiana Suhada Mohmad Tahiruddin and Siti Nurhazlin Jaluddin - Wan Ibrahim, Wan Nazihah; Mohmad Tahiruddin, Nordiana Suhada; Jaluddin, Siti Nurhazlin (Universiti Teknologi MARA, Perlis, 2013)
The aim of this study is to investigate the efficiency of different biosorbent materials for oil removal from polluted water. Three natural and chemically treated fibers of Banana, Durian, Jackfruits were utilized to absorb two types of oil namely diesel and petroleum from polluted water. The chemical modification of fruits fibers was carried out using acetic anhydride with absence and presence of N-bromosuccinimide (NBS) as catalyst has been investigated. The degree of acetylation was determined to measure the percentage of the fibers that has been modified in the sample. The chemical modification of the fruits fiber was evaluated by degree of acetylation method using FTIR Spectroscopy. This study also investigates the characterization of the fibers using FTIR spectrophotometer and Scanning Electron Microscopy (SEM). The comparison study between untreated and treated fibers was carried out with catalyst. The acetylated fiber show higher oil absorption capacity compare to untreated fiber due to increasing of hydrophobic properties on the surface of fiber. It was found that the weight percent gain increase up to 14% with using the catalyst compared to 7% without using catalyst. Thus, NBS was chosen as catalyst in this study.